Explanation:
Provided <u>2 length sides</u> and <u>one angle</u> also need to find <u>one missing side</u>.
So, use cosine rule:
a² = b² + c² - 2bc cos(A)
<h3><u>Part 1</u></h3>
c² = 9² + 11² - 2(11)(9) cos(57)
c² = 94.16147
c = √94.16147 = 9.70 cm
<h3><u>Part 2</u></h3>
d² = 5² + 7² - 2(5)(7) cos(48)
d² = 27.16
d = √27.16 = 5.21
<h3><u>Part 3</u></h3>
5² = 7² + 9² - 2(7)(9) cos(H)
-126cos(H) = 25 - 49 - 81
cos(H) = -105/-126
cos(H) = 5/6
H = cos⁻¹(5/6) = 33.56°
<h3><u>Part 4</u></h3>
8² = 4² + 7² - 2(4)(7) cos(J)
-56cos(J) = 64 - 16 - 49
cos(J) = -1/-56
J = cos⁻¹(1/56) = 88.98°
Passcode: 3142
[] signs mean that the number is included in the domain and () mean that the number is not included. Now,
1. [-1,5)
Because x is greater than or equal to -1 (included) but less than 5 (excluded
2. [-5,13)
When we plug in x = -1, we get the minimum value of -5, which is included because its x-value was included. The, we plug in x = 5 to find the range's maximum and this is excluded because its x-value was excluded.
3. 218
x = 6 lies in the domain of the first function so we will use it to evaluate the value of x = 6. We do this by simply substituting x into the function.
4. 12
x = 9 is included in the domain of the second function and the value of the second function at all points is 12.
5. 103
x = 10 is included in the domain of the second function so we will use it to evaluate the value of x = 10. This is done by substituting x into the equation.
Answer:
(1,2)
Step-by-step explanation:
x+4y = 9
2x -4y= -6
Add the equations together
x+4y = 9
2x -4y= -6
-------------------
3x +0y = 3
3x=3
Divide by 3
3x/3 = 3/3
x=1
Now find y
x+4y = 9
1 +4y =9
Subtract 1 from each side
4y = 8
Divide by 4
4y/4 = 8/4
y =2
The linear combination method is the same as the elimination method. Let's multiply the second equation by -2 so the x terms cancel each other out. When we do that we get a system of
![2x-3y=13](https://tex.z-dn.net/?f=2x-3y%3D13)
and
![-2x-4y=8](https://tex.z-dn.net/?f=-2x-4y%3D8)
. The x-terms cancel each other out giving us
![-7y=21](https://tex.z-dn.net/?f=-7y%3D21)
and y = -3. Now sub -3 into one of the equations to solve for x. x+2(-3)=-4, and x - 6 = -4. x = 2. So the solution for our system is (2, -3)
The answer is B. First solve the parentheses. Then make a quadratic equation and solve from there.